Implementasi Pendidikan Sejarah Studi Kasus: Tradisi Suroan Pada Masyarakaat Jawa di Desa Srikaton Kecamatan Tugumulyo Kabupaten Musi Rawas - Wafa Kamila; Syarifuddin; Alif Bachtiar Pamulaan (FIHROS: Jurnal Sejarah dan Budaya, 2025)
The Suroan tradition itself gave birth to Pancasila values which have had a positive impact on the community enviroment, especially in the educational enviroment. The implementation of the Suroan tradition has different methodes in each region, but has the same goal, namely to ask for blessing and protection from God Almighty.